2016
DOI: 10.1007/s11306-016-0985-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying metabolite markers for preterm birth in cervicovaginal fluid by magnetic resonance spectroscopy

Abstract: IntroductionPreterm birth (PTB) may be preceded by changes in the vaginal microflora and metabolite profiles.ObjectivesWe sought to characterise the metabolite profile of cervicovaginal fluid (CVF) of pregnant women by 1H NMR spectroscopy, and assess their predictive value for PTB.MethodsA pair of high-vaginal swabs was obtained from pregnant women with no evidence of clinical infection and grouped as follows: asymptomatic low risk (ALR) women with no previous history of PTB, assessed at 20–22 gestational week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 55 publications
2
55
0
Order By: Relevance
“…Vaginal bacterial communities dominated by L. jensenii usually have higher pH compared to when L. crispatus predominates (Aldunate et al ., 2015). We have previously observed that symptomatic women at risk of preterm birth show elevated cervicovaginal fluid acetate (Amabebe et al ., 2016a; Amabebe et al ., 2016b), which can be combined with pro-inflammatory mediators to improve its performance as a predictive marker (Amabebe et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Vaginal bacterial communities dominated by L. jensenii usually have higher pH compared to when L. crispatus predominates (Aldunate et al ., 2015). We have previously observed that symptomatic women at risk of preterm birth show elevated cervicovaginal fluid acetate (Amabebe et al ., 2016a; Amabebe et al ., 2016b), which can be combined with pro-inflammatory mediators to improve its performance as a predictive marker (Amabebe et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported the metabolic profile of women with and without BV using mass spectrometry-based metabolomics and classified women based on their vaginal metabolite composition 28 . Amabebe et al 29 www.nature.com/scientificreports www.nature.com/scientificreports/ hypothesized that the cervicovaginal ecosystem of commensal and pathogenic organisms could induce a specific metabolic profile that could be used for predicting the risk of PTD. In agreement with their previous report 29 , they demonstrated the potential of cervicovaginal acetate levels as a predictor of PTD using 1 H-NMR spectroscopy, especially in women with symptoms of PTL 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Identification of biomarkers in maternal serum or plasma provides a less invasive approach to identify women at risk for PTB. Gunko et al . used mass spectrometric profiling of maternal serum to identify the proteomic predictors of PTB.…”
Section: Proteomic Studies Of Ptbmentioning
confidence: 99%
“…47 Identification of biomarkers in maternal serum or plasma provides a less invasive approach to identify women at risk for PTB. Gunko et al 48 used mass spectrometric profiling of maternal serum to identify the proteomic predictors of PTB. Their findings detected changes in the production of 25 proteins with various regulatory functions namely proteolysis, angiogenesis, inflammation processes, transcription, and binding and transportation of various ligands that can predict the PTB as early as during the second trimester of pregnancy.…”
Section: Proteomic Studies Of Ptbmentioning
confidence: 99%